An Analysis of a Story Telling in a Conversation of Lamaholot Language Speakers - Elvis Albertus Bin Toni (Soshum: Jurnal Sosial dan Humaniora, 2018)
This study analyses a conversation among four Lamaholot speakers talking about Nipa Island Reclamation, a man-made island located in the border between Indonesia and Singapore. Three of the participants are migrant workers who live in Batam, Western Indonesia, and the other one is a student who live in Singapore. They met in Batam. Their conversation is video-taped and 12 minutes out of 49:13 minutes of the video content is transcribed and analysed. That question that this study aims to answer is what participants' contributions perfomed during the story is being told. It is revealed that the participants contribute in several ways. The contributions include initiating the proposed story and prompting the main speaker, questioning, co producing certain words, completing the gaps faced by the main teller and becoming a co teller. These findings confirm that the story telling in a conversation is a jointly work between a main teller and co teller.